Nitrogen cycling in the subtropical southeast Atlantic and southwest Indian Oceans as recorded by the nitrogen isotopes of modern planktic foraminifera - Granger, Robyn (Department of Oceanography, 2024)
Despite the importance of nitrogen (N) for ocean productivity, and the long history of using fossil foraminifera to reconstruct past ocean conditions, it is only in recent years, due to methodological advances, that the nitrogen isotope ratio (δ15N) of foraminifera has become a viable proxy for past marine nutrient cycling. Organic N trapped within planktic foraminifer shells is protected from bacterial degradation, with its δ15N recording the processes acting on the upper- ocean N pool. This thesis examines the relationship between local biogeochemi- cal cycling and foraminifera tissue- and shell-bound δ15N in the greater Agulhas Current system and southeast Atlantic Ocean, focusing on the implications for reconstructing Agulhas leakage (i.e., the transfer of Indian Ocean waters into the Atlantic). Past fluctuations in this important component of the Atlantic Meridional Overturning Circulation, whereby warm, saline Agulhas waters are transported to the North Atlantic along its upper limb, have been tied to global glacial-interglacial cycles, highlighting the region's sensitivity to large-scale cli- mate change. The work detailed in this thesis includes the first foraminifer- bound δ15N ground-truthing studies from the southeast Atlantic and the Agul- has Current regions and examines the extent to which the unique δ15N signature of Indian Ocean nitrate is preserved in the tissue and shells of foraminifera living in Agulhas leakage features (e.g., eddies). The isotopes of several forms of N, including nitrate, particulate organic N, size-fractionated zooplankton biomass, living foraminifera tissue and shell N, and fossil foraminifera, were measured and interpreted in the context of coincident hydrographic measurements to deter- mine the controls on the δ15N of foraminifera and their potential food sources. The data presented here reveal that mixed layer nitrate δ15N was noticeably lower within an Agulhas eddy than it was for the surrounding Cape Basin wa- ters, a characteristic that was likely inherited from low thermocline nitrate δ15N produced in the region of leakage origin, the Agulhas Current System. Simi- larly, the δ15N of foraminifera inhabiting the Agulhas eddy was found to be low relative to foraminifera under background southeast Atlantic conditions, despite foraminifera in the Agulhas Current System displaying on average a higher δ15N than was recorded by foraminifera inhabiting the eddy. The data therefore sug- gest that anticyclonic eddies “leaking” into the region from the Indian Ocean maintain a low-δ15N environment that sustains the growth of foraminifera for several months, and that N2 fixation and/or recycling of low-δ15N ammonium within the eddy environment likely contributed to lowering of foraminifer-δ15N. That foraminifer-δ15N is on average 2-3‰ lower in Agulhas leakage than in the southeast Atlantic suggests that enduring periods of increased leakage could result in relatively low-δ15N material being transferred to the sediment and recorded. A comparison of data from the southeast Atlantic and Agulhas regions to previous ground-truthing studies from the Sargasso Sea and Southern Ocean reveals similarities in both foraminifer tissue-shell δ15N relationships and inter- species δ15N differences. For instance, symbiont-hosting foraminifera are consis- tently lower in δ15N than deeper-dwelling, symbiont-barren individuals at the same location due to the symbiont's ability to recycle low-δ15N ammonium. Also consistent with previous studies is the positive correlation observed be- tween fossil foraminifera from core tops and modern shell- and biomass δ15N in the Atlantic, despite sediment being derived from multiple locations within the Cape Basin. This study adds to burgeoning efforts to ground-truth the foraminifer-δ15N palaeo-proxy and supports the argument that the δ15N of liv- ing foraminifera, which is set by both the local N supply and N-cycling processes, can be deduced from foraminifera shell-bound δ15N in the sediment record. Fur- thermore, the work detailed in this thesis examines how the unique δ15N of the nitrate and biological community of a particular water mass might be leveraged to reconstruct past variations in Agulhas leakage.